TEXT CONTENTION BEHIND SHARIA SUPERVISORY BOARD REPORTS: A CRITICAL DISCOURSE ANALYSIS - Ermawati, Ari; Birton, M Nur A; Tarmizi, Irfan; Muttaqin, Muhammad (UI Scholars Hub, 2021)
Sharia Supervisory Board Reports (SSBRs) have an interest in convincing the public that entities supervised by a Sharia Supervisory Board (SSB) are sharia-compliant and reflective of Good Corporate Governance (GCG) practices. Failure in public convincing will be detrimental to Islamic banks’ reputation as well as the SSB’s image and credibility. This study aimed to critically assess how the SSB produces reports as texts to persuade the public using Critical Discourse Analysis (CDA). We analyzed four SSBRs from two Islamic Commercial Banks (ICBs) and two Islamic Business Units (IBUs) owned by other ICBs as well as interviews for data triangulation. We employed three of Halliday’s CDA structures for data analysis: text as microstructure as well as the context of situation and the context of culture as macrostructure. The results are as follows. First, microstructure analysis on SSB members’ performance and personality shows that language practices used to build their character and positive image at semantic and syntactic levels are in place. Second, the context of situation trilogy reveals that the SSB only focuses on language compiling practices to direct readers into a desired direction while maintaining its existence and legitimacy. Third, the context of culture indicates that the SSBRs become more concerned with formality than substance, annexing a manipulative potential on reality. Also, it is identified that the SSBRs serve only as a fullfilment of regulations or internationally applied guidelines of SSB roles.